2018
DOI: 10.1016/j.bbmt.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Aging and Hematopoietic Cell Transplantation

Abstract: Hematopoietic cell transplantation (HCT) is increasingly utilized as a treatment for malignancies in the elderly population. At the same time, research has elucidated the impacts of HCT on bone marrow progenitor cells, one of which is accelerated aging. Clonal hematopoiesis has also been observed to occur in the aging population, both with and without HCT. The interplay between natural aging, clonal hemoatpoiesis, and the effects of HCT on the bone marrow, has not yet been addressed. Herein we explore this rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Despite rapid advances in understanding disease biology and development of several novel therapies, allogeneic hematopoietic cell transplantation (AHCT) remains an important curative treatment option for these patients. Survival post-transplant depends on disease and patient characteristics [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite rapid advances in understanding disease biology and development of several novel therapies, allogeneic hematopoietic cell transplantation (AHCT) remains an important curative treatment option for these patients. Survival post-transplant depends on disease and patient characteristics [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, additional hallmarks of aging such as epigenetic alterations and telomere shortening have been implicated in post-transplant outcomes (56). Recently, several elegant clinical translational studies compared the biologic age of donor with that of the recipient age and showed that there was significant accelerated aging associated with HCT, manifested as a rapid increase of epigenetic age and telomere shortening (57,58).…”
Section: Epigenetic Aging and Telomeresmentioning
confidence: 99%
“…When performing hematopoietic cell transplantation, it is critical to assess the chronological as well as biological age of the patient. The biological age of the cells can be attained by evaluating their clonogenic capacity and telomere length [ 52 ]. The telomere length of autologous CD34 + cells did not have any influence on the clinical outcome in cardiomyopathy patients.…”
Section: Senescence and Its Effect On Stem Cell Biology Transplanmentioning
confidence: 99%